Zobrazování a neurostimulace v psychiatrii - Linhartová, Pavla; Svěrák, Tomáš; Kuhn, Matyáš; Bartečků, Elis; Theiner, Pavel; Kašpárek, Tomáš; Ustohal, Libor; Bareš, Martin (Psychiatrie (Praha, Print), 2017)
x